Fertility and rural electrification in Bangladesh - FUJII, Tomoki (Institutional Knowledge at Singapore Management University, 2017)
We use a household-level panel dataset from Bangladesh to examine the household-level relationship between fertility and the access to electricity. We find that the household's access to electricity reduces the change in the number of children by about 0.1 to 0.25 children in a period of five years in most estimates. This finding also applies to retrospective panel data and is robust to the choice of covariates and estimation methods. Our finding passes falsification test and corroborates with the predictions of our theoretical model on the households' time use and consumption pattern.